Exploring brand identity practice in video game start-ups : Industrial Marketing - Harding, Andreas (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
The video game industry is a rapidly growing industry due to technology advancements andhas made video games to a mass phenomenon. The diffusion of today’s technologies has created and expanded the video game market, both demographical and geographical, which has attracted more customers and increased the intensity of the competition. Companies in the industry have to professionalize their marketing processes and business strategies in a moreflexible and quickly fashion than before to be able to stay competitive. An overcrowded market with thousands of products released every year creates problems for actors to get recognized. The purpose of this dissertation has been therefore to study small start-ups brand identity in its inception phase within the video game industry to assist their brand strategic approach and be able to strengthen their competitive advantage in a saturated market. The dissertation has adopted the corporate brand identity matrix framework by Urde (2013) and investigated the brand-driven elements in a start-up context; thus, the framework has only been applied incorporation-setting where the companies are large and known. Five indie game developers from northern Sweden participated in the study’s field research. The dissertation shows that the corporate brand identity matrix is adaptable for start-ups and are not dependent on the company size. Findings confirm early signs of brand identity and found correspondence between competence and value proposition, expression and personality and culture and relationship, which address interconnection between its brand-elements and its brand core. The unique findings where they all show signs of social engagements, passion and a fan-centric ambition of doing business and most of all everyone had a “community first” approach and were more inspired to deliver value to its customers rather than how they can achieve value for themselves. A concept model for start-ups in the inception phase of the video game industry has been made based on the empirical ...